On the Validity of Environmental Performance Metrics - Semenova, Natalia (Journal of business ethics, 2015)
Different proprietary databases have been used extensively in research to assess the environmental performance and environmental risk of companies. This study explores the convergent validity of the environmental ratings of MSCI ESG STATS (formerly known as Kinder, Lydenberg, and Domini Research & Analytics; KLD), Thomson Reuters ASSET4 (ASSET4) and Global Engagement Services (GES). The study shows that the ratings have common dimensions, but on aggregate, they do not converge. On the environmental opportunity side, KLD environmental strengths, and ASSET4 and GES environmental performance metrics correlate highly and provide convergent scores for US companies from 2003–2011. On the environmental risk side, KLD environmental concerns converge with the GES environmental industry risk and company emissions from the ASSET4 database. Further analysis confirms that industry-related risks are drivers of company-specific environmental performance.